An overview on antimicrobial and wound healing properties of ZnO nanobiofilms, hydrogels, and bionanocomposites based on cellulose, chitosan, and alginate polymers. (1st January 2020) - Alavi, Mehran; Nokhodchi, Ali
Highlights: All recognized antibacterial and wound remedy mechanisms of ZnONPs are presented. Comparison of antibacterial and wound healing capacities of chitosan, cellulose, alginate. Micro/nano formulations of ZnONPs with chitosan, cellulose, and alginate. Challenges and future viewpoints of ZnO nanoparticles with polysaccharides. Abstract: Release of Zn 2+ ions from zinc oxide nanoparticles (ZnO NPs) is a major mechanism for oligodynamic activities of these metal oxide NPs against eukaryotic and prokaryotic microorganisms. In addition to this mechanism, ZnO NPs can form reactive oxygen species (ROSs) resulted from electron-hole formation under certain light wavelength. These properties with suitable biocompatibility and biodegradability of ZnO NPs compared to other metal NPs have caused higher applications of these nanomaterials in therapeutic and cosmetic fields. Recently, natural polymers including cellulose, chitosan, and alginate polymers have gained more attention as safe and cost-effective scaffold for wound healing. Both ZnO NPs and these polymers have not been able to satisfy related patients. In this way, the coupling of these materials and nanomaterials as nanocomposites (NCs) is an alternative way to increase the mechanical and antibacterial properties of wound-healing tissue scaffolds. Controllable release of Zn 2+ ions in physiological medium should be considered as an indispensable factor to obtain appropriate industrial formulation. Therefore, in this review, attempts were made to highlight particularly important antibacterial results of these NCs in recent investigations.